1985
DOI: 10.1163/22941932-90000916
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Zone Formation as a Resistance Mechanism of Elms to Dutch Elm Disease

Abstract: Host responses of elms susceptible and resistant to Dutch elm disease were histologically examined. In a time course study the susceptible elm clone Ulmus × hollandica 'Belgica' and U. × hollandica '390', a clone which shows a high degree of resistance to non-aggressive isolates and a moderate degree of resistance to aggressive isolates of Ophiostoma ulmi, were inoculated in twig or trunk with either an aggressive or a non-aggressive isolate of O. ulmi. For purposes of comparison, the susceptible elm U. americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 11 publications
4
32
0
4
Order By: Relevance
“…Resistance to DED is strictly associated with the host's capacity to quickly localize the infection, preventing the pathogen from both spreading in the vascular system (Sinclair et al 1975) and reaching the cambium (Shigo & Tippet 1981, Bonsen et al 1985. A systemic infection drastically reduces the hydraulic conductivity in the functional xylem, which in elms is limited to the current year ring (Ellmore & Ewers 1985), mainly because of embolism development and progression (Zimmermann & McDonough 1978, Newbanks et al 1983).…”
Section: Host Resistancementioning
confidence: 99%
“…Resistance to DED is strictly associated with the host's capacity to quickly localize the infection, preventing the pathogen from both spreading in the vascular system (Sinclair et al 1975) and reaching the cambium (Shigo & Tippet 1981, Bonsen et al 1985. A systemic infection drastically reduces the hydraulic conductivity in the functional xylem, which in elms is limited to the current year ring (Ellmore & Ewers 1985), mainly because of embolism development and progression (Zimmermann & McDonough 1978, Newbanks et al 1983).…”
Section: Host Resistancementioning
confidence: 99%
“…Compartmentalization was first proposed as a mechanism against spread of decay in trees by isolating the damaged tissues and replacing it by new functional tissues (Shigo and Marx 1977). Later it was reported that this mechanism that causes changes in anatomy and chemistry of xylem cells also has an important role in protecting trees against colonization by vascular pathogens (Bonsen et al 1985;Shigo 1984;Tippett and Shigo 1981;Manion 2003;Smith 2006). The principle of the compartmentalization lies in the establishment of four types of Bwalls^.…”
Section: Reactions Of Infected Trees and Recoverymentioning
confidence: 99%
“…Compartmentalization resulting from the inherent structure of the wood, in combination with changes in anatomy and chemistry of xylem after infection, was suggested to play important roles in protecting trees against colonization by vascular pathogens (Bonsen et al 1985;Manion 2003;Shigo 1984;Tippett and Shigo 1981;Smith 2006). However, although recovery from Verticillium wilt has been described not only for ash, but also for other tree species including almond and peach (Ciccarese et al 1990), apricot (Taylor and Flentje 1968;Vigouroux and Castelain 1969), pistachio (Paplomatas and Elena 1998), cocoa (Emechebe et al 1974), avocado (Latorre and Allende 1983), olive (López-Escudero and Blanco-López 2005), catalpa and sassafras (Kasson et al 2015), there is little information about the fate of the fungus in infected trees in the years following the initial infection.…”
Section: Introductionmentioning
confidence: 99%